Koneksi Politik dan Nilai Perusahaan: Apakah Mekanisme Corporate Governance Memiliki Peran? - Yeterina Widi Nugrahanti; Indriyani Nurfitri (AFRE (Accounting and Financial Review), 2022)
This study aims to examine the effect of political relations on firm value with corporate governance mechanisms as a moderating variable. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using the purposive sampling method with a sample of 158 companies during the 2018-2020 period. Data were analyzed by panel data regression for hypothesis testing. The results of this study indicate that political connections have a positive effect on firm value. The corporate governance mechanism in the form of managerial ownership and the size of the board of commissioners is proven to be able to moderate the influence of political connections on firm value, but independent boards of commissioners are proven unable to moderate the influence of political connections on firm value. This implies that companies need to optimize their political connections to increase the value of the company. This study also finds that the corporate governance mechanism in the form of managerial ownership and the size of the board of commissioners weakens the positive influence of political relations on firm value.DOI: https://doi.org/10.26905/afr.v5i2.7762